ANALISIS AKUISISI SAHAM TERHADAP PERUSAHAAN F DAN B STUDI KASUS PADA PT INDOFOOD CBP DAN PINEHILL COMPANY LIMITED - Fitri Ramadhani; M. Fadhlan Rohmani; M.Masrukhan (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2024)
One tactic frequently employed by businesses to broaden their market, boost their competitiveness, and enhance operational effectiveness is stock purchase. Acquisitions can give food and beverage (F&B) businesses direct access to the target company's clientele, manufacturing capacity, and distribution network. This research especially looks at the acquisition of Pinehill firm Limited, a global F&B firm, by PT Indofood CBP Sukses Makmur Tbk (ICBP). Pinehill has a reasonably large network, particularly in the Middle East and Africa, whereas ICBP, a member of the Indofood group, is regarded as one of the leading players in Indonesia's food and beverage business. The findings demonstrate how the purchase of Pinehill greatly boosts ICBP's earnings and opens up new markets in Asia, Africa, and the Middle East. Short-term profitability is impacted by the increased financial load that comes with taking on more long-term debt to finance acquisitions.